(untitled) (Journal of history, 2025)
The article analyzes the inequality and injustice of internally displaced Poles during World War II, complaints, protests and their relations with the Soviet government and the representative office of the Embassy of the Republic of Poland, and discusses the fruitful work of the representative office of the Embassy of the Republic of Poland in the Soviet Union, which used various political mechanisms aimed at improving the political and social situation of Poles. In foreign and domestic historiography, the role of this organization in the development of the country has not been adequately studied or critically evaluated. Due to a focus on individual political events related to the war, the presence of the foreign political authority within the Soviet system has not been fully appreciated. The analysis of archival documents reveals that this organization played a significant role in exposing the inefficiencies, gaps, and contradictions within the Soviet system. Along with the source analysis of archival documents, comparative historical, problem-solving, and synthesis methods were employed. The institutional method was used to analyze the relationship between the Soviet government and the representative office of the Embassy. The resolution of numerous Polish issues by the representative office of the Embassy of the Republic of Poland and their involvement in political life resulted in persecution of their employees. In summary, such repressive measures were aimed at suppressing and eliminating the political freedom of the Polish people.